HUBUNGAN KOMITMEN, KOMPETENSI SERTA KEMAMPUAN PADA KINERJA PROTOKOL DI SETDA PROVINSI JAWA TIMUR - Rismawati, Rismawati (Jurnal Ilmiah Manajemen dan Bisnis (JIMBis), 2022)
The purpose of this study is to analyze the influence of commitment, competence and capability in improving employee performance at the Protocol Section of the Sertda of East Java Province. This study uses a quantitative method with an explanatory approach. The data collection used is observation, distributing questionnaires and documentation. The population used is all protocol staff employees at the Regional Secretariat of East Java Province, totaling 92 employees. However, the sample used was only 50 employees who were directly involved in this study. The results of this study indicate that the results of the t-test state that commitment can have a positive and significant influence in improving employee performance at the protocol section of the Sertda of East Java Province. However, competence and capability have no significant effect on employee performance at the Regional Secretariat of East Java Province.